MultiObjective robust network design under uncertain traffic an approach based on evolutionary algorithm - Arteta, Adolfo; Pinto-Roa, Diego P. (2015 Latin American Computing Conference (CLEI), 2015)
Given the importance and complexity of the problem of robust network design, this work, studies the robust network design subject to guarantee certain level of quality of service, so that the reservation of an adjustable bandwidth for each node, the network is not negatively influenced by traffic from the rest of the network. Therefore a MultiObjective Evolutionary Algorithm (MOEA) is proposed to solve and find the robust network design, inspired by the concept of price of robustness, which simultaneously minimizes the cost of network, inequity traffic and maximizes the traffic service in the worst case scenario. Finally, experimental results show the benefits of the proposed approach to get a set of non-dominated solution on which it can make, a better decision making.